AN ANALYSIS OF LECTURER TALK DURING TEACHING AND LEARNING PROCESS OF ENGLISH AS A FOREIGN LANGUAGE - Siti Jubaidah; Rusfandi Rusfandi (JURNAL ILMIAH BAHASA DAN SASTRA, 2019)
Researching teacher talk during teaching and learning process of English is essential because it offers practical implications for the improvement of teaching and learning process. However, there are still few studies which try to compare types of talk used by lecturers who teach content and skill subjects. This research investigates the types and the dominant types of lecturer talk during the teaching and learning process at an English Education Department. The participants were two English lecturers at a private University in Malang who taught Vocabulary (skill subject) and Poetry (content subject) classes. The researchers used an audio recorder to record the utterances by the lecturers. The data were analyzed qualitatively by using FIAC (Flanders Interaction Analysis Category). The types of lecturer talk produced by the lecturer who taught Vocabulary were Ask question, Give direction, Give lecture, Accept or use students’ idea, Praise or encourage, and Criticize or justify authority. The types of lecturer talk produced by the lecturer who taught Poetry were Give lecture, Ask question, Accept or use students’ idea, Give direction, Praise or encourage, and Criticize or justify authority. The most dominant types of talk produced by the lecturer who taught Vocabulary were Ask question and Give direction but Give lecture was the most dominant types of talk produced by the lecturer who taught Poetry. This finding indicates that types of course taught by lecturers affect the kinds of talk produced by the lecturers.